Sententia Minuciorum/Tabula Polcevera from 117 BCE – arbitration as an instrument for resolving disputes among allies during the Republican period and a source to analyse Rome’s policy regarding subordinate lands - Maciej Piegdoń (In Gremium. Studies in History, Culture and Politics, 2025)
Sententia Minuciorum/Tabula Polcevera from 117 BCE – arbitration as an instrument for resolving disputes among allies during the Republican period and a source to analyse Rome’s policy regarding subordinate lands. The Sententia Minuciorum/Tabula Polcevera gives an insight into the proceedings before the Roman arbitrators. It is not just a judgment of two officials, but a document that also describes the legal acts and actual actions taken by them in Liguria. The arbitrators dealt with the conflict between the inhabitants of Genoa and the castellum of the Viturii Langenses/Langates and the tribes living in the neighboring areas for the use of the ager publicus. The inscription also allows you to get to know the backstage of Roman policy towards subordinate inhabitants. It is an example of a document showing the moment of arranging internal relations in the conquered territories, a phase that is usually missed due to the limited source material.